Utilisation of the Coherence Analysis in Acoustic Diagnostics of Internal Combustion Engines - DĄBROWSKI, Zbigniew; DZIURDŹ, Jacek; GÓRNICKA, Dorota (Archives of Acoustics, 2017)
The leading thought of the present text is that the internal combustion engine noise – regardless of all possible inconveniences – is a good information carrier that allows for the explicit diagnostics of such subtle defect as the valve face decrement which is so small that it is in practice ‘unnoticeable’ by the standard diagnostic-controlling system of a passenger car. However, such defect at its further propagation can be much more dangerous. Thus, diagnosing its initial state is worth trying. This study is a continuation of investigations where efforts were undertaken to perform the efficient diagnostics on the bases of observations and analyses of mechanical vibrations of the engine head.